Mainstreaming gender in agricultural R&D - CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation (CGIAR System Organization, 2009)
Mainstreaming a gender perspective is the process of assessing the implications for women and men of any planned action, including legislation, policies or programmes in all areas and at all levels. It is a strategy for making women's as well as men's concerns and experiences an integral dimension of teh design, implementation, monitoring and evaluation of policies and programmes in all political, economic and societal spheres so that women and men benefit equally and inequality is not perpetuated.